Habitus transition experience among Yemeni Community leaders in Malaysia - Albahri, Nabil Mohsen (2017)
The study explores the habitus transition experience of the Yemeni Community leaders in Malaysia (YCM leaders) and how this experience affected their perspectives, beliefs, behaviors and practices of community leadership. YCM leaders' experience of community leadership had two major issues; their relationship with each other and their relationship with the Malaysian society ecological system, i.e., the surrounding environmental context. This study was designed to address this research gap by exploring YCM leaders, as participants, and experiences of habitus developmental changes regarding community leadership. This process of investigation will lead to understanding the change and the YCM leaders’ mechanisms of adapting and learning from the Malaysian sociocultural context, i.e., the micro- meso- exo- and macro-system. It will explore the factors in the local context that influence this developmental change other than religion and the process of reforming the perception of the community leader. This study has four objectives that were organized to close this gap by; (a) exploring YCM leaders’ perspective and behavioral changes about community leadership, (b) understanding how YCM leaders contest for the position of community leader (c) exploring the influence of the Malaysian ecological system context on YCM leaders’ habitus transition, and (d) investigating the challenges that YCM leaders are facing especially YCM women leaders. The study has utilized the qualitative case study methodology that included participants' observations, semi-structured interviews and documents analysis to the 12 YCM leaders who have been living in Malaysia for more than six years and who have played leadership roles among the Yemeni Community in Malaysia. The first finding of the study indicated that YCM leaders have been experiencing gradual habitus transition of perspective and practice regarding community leadership from the Yemeni environmental context to the Malaysian one. The second finding of the study indicated that YCM leaders have been experiencing shift in contesting and competing for the community leadership position. They are competing for the position by accumulating resources, skills and knowledge rather than claiming biological right to it. The third finding of the study indicated that YCM leaders have been influenced by the Malaysian environmental context in many ways according to the length of time they spent in Malaysia and the level of engagement with the Malaysian environmental context. The fourth finding of the study indicated that YCM leaders and YCM women leaders have been experiencing multiple challenges as they exercise community leadership. The main challenges they face are; the homeland environmental habitus regarding the interrelations and the Islamists’ interpretations of women's roles. This idea may enhance and develop YCM future generations as Yemeni students’ and community leaders’ understanding about the perspective and practices of community leadership become similar to the local practices. YCM educational council may initiate programs for educating and training the next generation about fair and normative social contracts and arrangements that create peace and harmony among the socially and socio-politically unstable Islamic societies such as that of Yemen. The outcomes of this research have emerged to contribute in bridging the gap that has existed relating to theory and practice of community leadership development as well as the individuals' socialization and interrelationship dynamics.